The Effect of Environmental, Social, and Governance (ESG) Disclosure on Company Value in Manufacturing Companies Listed on the Indonesia Stock Exchange in 2019-2022 - Abni Lahaya, Ibnu; Triadita, Dristi Putri (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
This study aims to determine the influence of each ESG disclosure on company value in manufacturing companies listed on the Indonesia Stock Exchange in 2019-2022. The data sources used come from secondary data in the form of annual reports and sustainability reports, and are analyzed by panel data regression using Eviews 12. The number of samples used in this study is 17 samples with a total of 68 companies in 4 periods of observation. The results of the study show that 1) Environmental Disclosure has a positive and significant influence on company value, 2) Social Disclosure has no influence on company value, 3) Governance Disclosure has a positive and significant influence on company value. The managerial implications of this research are to continue to maintain and improve the disclosure of environmental and governance information, as well as to improve social disclosure in sustainability reports. This is based on research findings that show that comprehensive disclosure has the potential to increase a company's value